2020
DOI: 10.3390/su122310091
|View full text |Cite
|
Sign up to set email alerts
|

Fish Losses for Whom? A Gendered Assessment of Post-Harvest Losses in the Barotse Floodplain Fishery, Zambia

Abstract: Few studies examine post-harvest fish losses using a gender lens or collect sex-disaggregated data. This mixed-methods study assessed fish losses experienced by female and male value chain actors in a fishery in western Zambia to determine who experiences losses, why, and to what extent. Results indicate that participation in the fishery value chain is gendered and most losses occur during post-harvest activities. Discussions with fishers, processors, and traders suggest the value chain is more fluid than ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The extent of post-harvest fish loss affects men and women differently ( Kaminski et al., 2020 ; Kruijssen et al., 2020 ). Female fishers, especially the older ones, are involved in the collection of invertebrates, nearshore fishing and processing activities such as frying, drying and smoking, which reduce spoilage.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The extent of post-harvest fish loss affects men and women differently ( Kaminski et al., 2020 ; Kruijssen et al., 2020 ). Female fishers, especially the older ones, are involved in the collection of invertebrates, nearshore fishing and processing activities such as frying, drying and smoking, which reduce spoilage.…”
Section: Discussionmentioning
confidence: 99%
“…The females reported shorter selling times for their catch than the males (10.1 vs. 13, hrs respectively), reducing the spoilage. Additionally, larger species of fish spoil easily and take longer to process compared to the invertebrates collected by females ( Kaminski et al., 2020 ). However, related studies have reported more physical losses in females than in male fishers ( Kaminski et al., 2020 ; Kruijssen et al., 2020 ), because females rely on the labour of males to operate fishing vessels or carry heavy consignments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations